The Relationship Between the Activity of Scouting and Learning Outcomes of Students at SMPN 40 Padang - Abdi Amulya; Irmawita Irmawita (Universitas Negeri Padang, 2020)
The background of this study is about the activity of scouting the students SMPN 40 Padang is a low category and very influential on the learning achievement of students obtained. The purpose of this research is to see the levels and relationship of scouting organizational effectiveness and learning outcomes of students SMPN 40 Padang. The type of this research is correlational with a quantitative approach. The sample of this study consisted of 30 students in SMPN 40 Padang by using random sampling data collection. The instrument of this study used a questionnaire about scouting organizational activeness consisting of 17 questions and data about the learning achievement of students of SMPN 40 Padang. From this research, it can be concluded that the level of activity in the scouting organization with the learning achievement of students at SMPN 40 Padang is categorized as low, because it can be seen from the results of the questionnaire that students responded (48.50%) rarely and never (25.40%). Meanwhile, seen from the learning outcomes of students (36.7%) in the low category and very low (10%). This is evidenced by the calculation of the correlation using the moment product formula which shows the results that recount (0.548) is greater than rtable at the 95% confidence level (0.361) and rtabel for the 99% confidence level (0.463) so that the researchers get quite significant results. The relationship is quite significant with a significance level of 99% so that the low activity of scouting organizations followed by students can also affect the learning achievement of students at SMPN 40 Padang.Keywords: Scouting organizational activeness, learning outcomes